CAUSES OF DEVELOPMENT LIVER ABSCESSES - M. R. Garayev; A. I. Gritsayenko; M. A. Nartaylakov; V. D. Dorofeyev (Креативная хирургия и онкология)
Liver abscesses of various origins are the group of severe purulent diseases of the liver and it is considered one of the difficult problems of the hepatobiliary system. The article presents the current data on the causes and microbiological composition of pathogens liver abscesses.